Analisis Validitas Media Augmented Reality of Optic (ARTIC) Berbasis Android Pada Materi Alat Optik - Muafa, Arif; Anggaryani, Mita (IPF: Inovasi Pendidikan Fisika, 2024)
There are many studies related to the development of learning using technological advances, one of which is augmented reality. This developed learning media, ARTIC, is a media developed to train students' science literacy skills by utilising augmented reality technology to bring up 3D objects on optical instrument material. This research focuses on analysing the validity of the ARTIC media that has been developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development research model. Media validation was conducted by two validators who are expert lecturers in the field of learning media. Media validity was reviewed from four aspects, namely aspects of display design, programme operation, navigation, and usefulness. The results showed that the validity scores obtained in the four aspects were 94%, 98%, 100%, and 95%. So that the average percentage score of ARTIC media validation is 96% with a very valid category. So it can be stated that ARTIC media is feasible to be used as learning media to train students' science literacy in physics learning on optical devices material.